Media Reporting of Practice-Changing Clinical Trials in Oncology: A North American Perspective. (26th February 2016) - Andrew, Peter; Vickers, Michael M.; O'Connor, Stephen; Valdes, Mario; Tang, Patricia A.
Abstract: Introduction: Media reporting of clinical trials impacts patient-oncologist interactions. We sought to characterize the accuracy of media and Internet reporting of practice-changing clinical trials in oncology. Materials and Methods: The first media articles referencing 17 practice-changing clinical trials were collected from 4 media outlets: newspapers, cable news, cancer websites, and industry websites. Measured outcomes were media reporting score, social media score, and academic citation score. The media reporting score was a measure of completeness of information detailed in media articles as scored by a 15-point scoring instrument. The social media score represented the ubiquity of social media presence referencing 17 practice-changing clinical trials in cancer as determined by the American Society of Clinical Oncology in its annual report, entitled Clinical Cancer Advances 2012; social media score was calculated from Twitter, Facebook, and Google searches. The academic citation score comprised total citations from Google Scholar plus the Scopus database, which represented the academic impact per clinical cancer advance. Results: From 170 media articles, 107 (63%) had sufficient data for analysis. Cohen's κ coefficient demonstrated reliability of the media reporting score instrument with a coefficient of determination of 94%. Per the media reporting score, information was most complete from industry, followed by cancer websites, newspapers, and cable news. The most commonly omitted items, in descending order, were study limitations, exclusion criteria, conflict of interest, and other. The social media score was weakly correlated with academic citation score. Conclusion: Media outlets appear to have set a low bar for coverage of many practice-changing advances in oncology, with reports of scientific breakthroughs often omitting basic study facts and cautions, which may mislead the public. The media should be encouraged to use a standardized reporting template and provide accessible references to original source information whenever feasible. Abstract : This study aimed to characterize the accuracy of media and Internet reporting of practice-changing clinical trials in oncology. Based on media reporting, social media, and academic citation scores, it was determined that media outlets appear to have set a low bar for coverage of many practice-changing advances in oncology, with reports of scientific breakthroughs often omitting basic study facts and cautions.